Novel red fluorophores with superior performance in STED microscopy - Wurm, Christian A. (2012)
In optical microscopy, most red-emitting dyes provide only moderate performance due to unspecific binding, poor labeling efficiency, and insufficient brightness. Here we report on four novel red fluororescent dyes, including the first phosphorylated dye, created by combining a rigidized rhodamine backbone with various polar groups. They exhibit large fluorescence quantum yields and improved NHS ester stability. While these fluorophores are highly suitable for fluorescence microscopy in general, they excel in stimulated emission depletion (STED) microscopy, providing < 25 nm spatial resolution in raw images of cells. © 2012 Wurm et al.